Fluorescence, Antibacterial and Pigmentation Studies of Some Binuclear Schiff Bases Complexes - A. Zabin, Sami; Jejurkar, C.R. (Asian Journal of Chemistry, 2010)
Four Schiff bases derived from thiocarbohydrazide and salicylaldehyde, o-vanilline, 2,4-dihydroxybenzaldehyde or 2-hydroxy-1-naphthaldehyde have been synthesised and their twelve metal complexes of Cu(II), Ni(II) and Zn(II) have been isolated. The complexes are characterised by elemental analysis, electronic and IR spectral studies, magnetic measurements and X-ray diffraction studies. The complexes have been studied for their fluroscence, antibacterial and pigmentation properties. Complexes show lower fluorescence intensity compared to ligands. The ligands and their metal complexes show good antibacterial activities. The complexes are also found to be good pigments as they possess higher light and rubbing fastness. These properties have been explained on the basis of structural elucidation, charge transfer and intercomponent energy transfer.